2017
DOI: 10.3390/mi8080230
|View full text |Cite
|
Sign up to set email alerts
|

A Droplet Microfluidics Based Platform for Mining Metagenomic Libraries for Natural Compounds

Abstract: Historically, microbes from the environment have been a reliable source for novel bio-active compounds. Cloning and expression of metagenomic DNA in heterologous strains of bacteria has broadened the range of potential compounds accessible. However, such metagenomic libraries have been under-exploited for applications in mammalian cells because of a lack of integrated methods. We present an innovative platform to systematically mine natural resources for pro-apoptotic compounds that relies on the combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Those observations have practical implications because we have shown that microfluidic droplets can be used to generate highly controlled cell aggregates for high-throughput screening. 67 Remarkably, a simple overlay experiment can reveal some properties of surfactants at molecular scale at the interface.…”
Section: Resultsmentioning
confidence: 99%
“…Those observations have practical implications because we have shown that microfluidic droplets can be used to generate highly controlled cell aggregates for high-throughput screening. 67 Remarkably, a simple overlay experiment can reveal some properties of surfactants at molecular scale at the interface.…”
Section: Resultsmentioning
confidence: 99%
“…In an interesting approach to screen for proapoptotic compounds, Theodorou et al mixed bacteria in microfluidic droplets with mammalian cells, which could be assayed for apoptosis markers. 468 For the foreseeable future, these complicated screening problems will have to be solved on a case-by-case basis.…”
Section: Novel Enzymes and Enzymatic Reactions Leading To Total Synthesis Of Complex Natural Productsmentioning
confidence: 99%
“…The combination of droplet microfluidics and optofluidics, coined hereafter as droplet optofluidics, offers many prospects spanning many academic and industrial fields in biology, chemistry, physics, material, and interface sciences [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. For instance, it enabled the identification of very rare gene sequences [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], screening of cells or bacteria [ 52 ], membrane proteins inhibitors screening [ 53 ], coupled optical lab-on-chip platform with small angle X-ray scattering (SAXS) [ 54 ], and engineering microparticles for photonics applications [ 55 , 56 ], on-chip multiphasic tunable grating [ 57 ], reconfigurable droplet grating [ 58 ], fluidic Michelson interferometer [ 59 ], droplet grating with polydimethylsiloxane (PDMS) air-lens waveguide setup [ 60 ], 3D and 4D optically fabricated complex geometries [ 61 , 62 ], reconfigurable compound micro-lenses [ 63 ], and countless other possibilities. Previous examples may be considered to be the state-of-the-art, and the domain is flourishing day-by-day to new trends.…”
Section: Introductionmentioning
confidence: 99%